Waiting for Unruh - Fewster, Christopher J.; Juárez-Aubry, Benito A.; Louko, Jorma (IOP Publishing, 2016)
How long does a uniformly accelerated observer need to interact with a quantum field in order to record thermality in the Unruh temperature? We address this question for a pointlike Unruh–DeWitt detector, coupled linearly to a real Klein–Gordon field of mass and treated within first order perturbation theory, in the limit of large detector energy gap . We first show that when the interaction duration is fixed, thermality in the sense of detailed balance cannot hold as , and this property generalises from the Unruh effect to any Kubo–Martin–Schwinger state satisfying certain technical conditions. We then specialise to a massless field in four spacetime dimensions and show that detailed balance does hold when grows as a power-law in as , provided the switch-on and switch-off intervals are stretched proportionally to and the switching function has sufficiently strong Fourier decay. By contrast, if grows by stretching a plateau in which the interaction remains at constant strength but keeping the duration of the switch-on and switch-off intervals fixed, detailed balance at requires to grow faster than any polynomial in , under mild technical conditions. The results also hold for a static detector in a Minkowski heat bath. The results limit the utility of the large regime as a probe of thermality in time-dependent versions of the Hawking and Unruh effects, such as an observer falling into a radiating black hole. They may also have implications on the design of prospective experimental tests of the Unruh effect.